1989
DOI: 10.1161/01.atv.9.5.614
|View full text |Cite
|
Sign up to set email alerts
|

Alimentary lipemia-induced redistribution of cholesteryl ester between lipoproteins. Studies in normolipidemic, combined hyperlipidemic, and hypercholesterolemic men.

Abstract: 2 It has been suggested that, after hydrolysis of triglyceride, cholesteryl ester in remnant particles can be deposited in the arterial wall.34 Cholesteryl ester in chylomicrons and chytomicron remnants can be derived from the intestine 5 or from other lipoproteins present in plasma by the action of lipid transfer

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
9
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(12 citation statements)
references
References 39 publications
3
9
0
Order By: Relevance
“…45 Moreover, it has been proposed that the elevated plasma CETP levels observed in endogenous hyperlipidemia result in increased CETP gene expression by a mechanism similar to that involving dietary cholesterol. 46 These observations strongly suggest that elevation in CETP mass or activity during postprandial lipemia, as reported by others, 27,44 is above all the consequence of the amount of exogenous cholesterol consumed. In addition, the increase in plasma CETP levels observed by others 27,44 ranged from 5% to 12%, thereby suggesting heterogeneity in postprandial response in terms of increase in plasma CETP levels within normolipidemic subjects.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…45 Moreover, it has been proposed that the elevated plasma CETP levels observed in endogenous hyperlipidemia result in increased CETP gene expression by a mechanism similar to that involving dietary cholesterol. 46 These observations strongly suggest that elevation in CETP mass or activity during postprandial lipemia, as reported by others, 27,44 is above all the consequence of the amount of exogenous cholesterol consumed. In addition, the increase in plasma CETP levels observed by others 27,44 ranged from 5% to 12%, thereby suggesting heterogeneity in postprandial response in terms of increase in plasma CETP levels within normolipidemic subjects.…”
Section: Discussionsupporting
confidence: 63%
“…46 These observations strongly suggest that elevation in CETP mass or activity during postprandial lipemia, as reported by others, 27,44 is above all the consequence of the amount of exogenous cholesterol consumed. In addition, the increase in plasma CETP levels observed by others 27,44 ranged from 5% to 12%, thereby suggesting heterogeneity in postprandial response in terms of increase in plasma CETP levels within normolipidemic subjects. Similar conclusions may be reached from analysis of data with respect to changes in plasma CETP activity during postprandial lipemia.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…However, because humans will be mostly PP lipemic during the day owing to consumption of regular meals, LCAT-and CETP-mediated transformation of UC on cell membranes into chylomicron CEs may occur throughout the PP lipemic period in vivo. A number of studies [38][39][40] have shown PP chylomicronemia to be accompanied by a significant net decrease in LDL and HDL CE level as well as total plasma CE levels or a significant shift in the distribution of CEs from LDL and HDL to PP chylomicrons. The PP decreases in LDL and HDL CE levels were proportional to the increases of plasma TGs in PP plasma or the amount of fat ingested.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that CEs that were first transferred from HDL to LDL were then transferred secondarily to CMs during PP phases (9). Induction of PP lipemia accompanies an increase in the plasma activities of both LCAT and CETP (15)(16)(17) and a net decrease in CE levels on both LDL and HDL, as well as in plasma total CE levels (18), and a shift in the distribution of CEs from endogenous lipoproteins to CMs (19). These observations suggest that CMs appearing in PP plasma may serve as acceptors of CEs from both LDL and HDL.…”
mentioning
confidence: 96%